IMPLEMENTASI PEMASARAN GELOMBANG BARU STRATEGI 4.0 DI BANK SYARIAH INDONESIA - Lidya Anggraeni (AT-TIJARAH: Jurnal Penelitian Keuangan dan Perbankan Syariah, 2022)
This Study aims to examine the implementation of marketing strategies at Bank Syariah Indonesia tbk KCP Sipin Soemantri using the New Wave Marketing concept, as wellas describe what can encourage and become obstacles in the use of the New Wave Marketing concept. The method used in this research is descriptive qualitative through observation and interview procedures, then the data is summarized and verified its validity with triangulation technique. Conclusion in this study: New Wave Marketing strategies have been implemented, including brand is care, and process is collaboration. Altough there are several aspects that have not been implemented in brand is character where the percentage of customer data that advocates for BSI Mobile services has not been carried out. Internal support by the head office through the provision of information on BSI Mobile services and quick responses to problem solving, external supportis feedback from users and non users of BSI Mobile service. Furthemore, internal obstacles are the new system, as well as external , namely there are still those who refuse to use the BSI Mobile services in various ways. The reason, especially the elderly who are not ready to change technology.